Ujaran Kebencian di Game Online Mobile Legends: Bang Bang Ditinjau dari Undang-Undang No. 19 Tahun 2016 tentang Perubahan atas Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Rhenovan Jody Refasan Hermawan; Ade Mahmud (Bandung Conference Series: Law Studies, 2024)
Abstract. According to Law No. 19 of 2016 concerning amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, Article 28 paragraph (2) contains "Every person who intentionally and without right distributes and/or transmits Electronic Information and/or Documents Electronics whose nature is to incite, invite or influence other people so as to create feelings of hatred or hostility towards certain individuals and/or groups of people based on race, nationality, ethnicity, skin color, religion, belief, gender, mental disability or physical disability shall be punished with a maximum prison sentence of 6 (six) years and/or a maximum fine of IDR 1,000,000,000.00 (one billion rupiah).” The research methodology used includes several approaches, including qualitative content analysis of player interactions in games, comprehensive literature studies regarding the ITE Law and other related regulations, interviews with players, game moderators, and cyber law experts, as well as comparative analysis with the treatment and handling of hate crimes. in other countries, especially in the context of online gaming. Abstrak. Menurut Undang – Undang No 19 Tahun 2016 Tentang perubahan atas Undang – Undang No 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik Pasal 28 ayat (2) berisi “Setiap Orang yang dengan sengaja dan tanpa hak mendistribusikan dan/atau mentransmisikan Informasi Elektronik dan/atau Dokumen Elektronik yang sifatnya menghasut, mengajak, atau memengaruhi orang lain sehingga menimbulkan rasa kebencian atau permusuhan terhadap individu dan/atau kelompok masyarakat tertentu berdasarkan ras, kebangsaan, etnis, warna kulit, agama, kepercayaan, jenis kelamin, disabilitas mental, atau disabilitas fisik dipidana dengan pidana penjara paling lama 6 (enam) tahun dan/atau denda paling banyak Rp1.000.000.000,00 (satu miliar rupiah)”. Metodologi penelitian yang digunakan menggabungkan beberapa pendekatan, termasuk analisis konten kualitatif terhadap interaksi pemain dalam game, studi pustaka komprehensif mengenai UU ITE dan regulasi terkait lainnya, wawancara dengan pemain, moderator game, dan ahli hukum siber, serta analisis komparatif dengan regulasi dan penanganan ujaran kebencian di negara lain, khususnya dalam konteks game online.